Analisis Sentimen Netizen Indonesia Terhadap Kampanye Penggunaan Kecerdasan Buatan Oleh Pemerintah Menggunakan Algoritma Naive Bayes - Kardandi Alfarizi Siregar; Salsabila Nasution; Putri Nabawy (Jurnal Ilmu Komputer dan Informatika | E-ISSN : 3063-9026, 2025)
he development of artificial intelligence (AI) has encouraged the Indonesian government to adopt this technology in various public service sectors. However, the use of AI has received various responses from the public, especially on social media. This study aims to analyze the sentiment of Indonesian netizens towards the government's campaign to use AI using the Naive Bayes algorithm. Data were collected from the Twitter platform and analyzed through preprocessing, sentiment classification, and model evaluation stages. The results of the study show that the majority of netizen sentiment is negative, with concerns regarding injustice for creative workers, lack of regulation, and the use of AI for political interests. This study is expected to be an input for the government in designing a more ethical and inclusive AI adoption policy.